A hybrid piezoelectric nanogenerator comprising of KNN/ZnO nanorods incorporated PVDF electrospun nanocomposite webs. (5th March 2020) - Bairagi, Satyaranjan; Ali, Syed Wazed
Summary: A unique potassium sodium niobate (KNN)/zinc oxide (ZnO) incorporated Poly(vinylidene fluoride) (PVDF) polymer‐based hybrid piezoelectric nanogenerator has been developed by using electrospinning process. Electrospinning method has been used due to its remarkable role in improving the piezoelectric performance of the nanocomposite based nanogenerator by providing mechanical stretching and in situ poling of both the polymer as well as filler at the same time. The PVDF/KNN/ZnO electrospun nanocomposite‐based piezoelectric nanogenerator exhibits the maximum output voltage as compared to PVDF/KNN and PVDF/ZnO based nanogenerator. The output voltage and current for the PVDF/KNN/ZnO based nanogenerator are 25 V and 1.81 μA (when pressure is applied by the finger tapping mode) and 8.31 V and 5 μA (when pressure is applied by standard sewing machine). The synergistic effect of KNN and ZnO nanorods into PVDF polymer matrix significantly improves the resultant piezoelectric performance of the PVDF/KNN/ZnO based nanogenerator by which it has been possible to glow an LED, power density of 11.31 μW/cm 2 (finger tapping) and 10.38 μW/cm 2 (pressure applied by sewing machine). Finally, the practical applicability of the produced nanogenerator has been checked by attaching it on elbow and wrist of a human hand, which shows 90 mV (for elbow), 400 mV (front side of wrist), and 225 mV (back side of wrist) output voltage by bending and moving of the same. Abstract : Amalgamation of potassium sodium niobate (KNN) and zinc oxide (ZnO) nanorods into the PVDF polymer‐based nano fibrous matrix Synergistic functions of KNN and ZnO in the nanocomposites performs a unique role in piezoelectric performance of hybrid nanogenerator. A breakthrough study where only 3% KNN NRs and 2% ZnO have served a novel purpose of enhancing the piezoelectric property and without any subsequent poling requirement PVDF/KNN/ZnO NRs nanocomposite‐based fibrous nanogenerator could generate around 25 V output voltage The maximum current obtained from nanogenerator is 1.81 μA and power density recorded is 11.31 μW/cm 2